2015
DOI: 10.1515/amm-2015-0275
|View full text |Cite
|
Sign up to set email alerts
|

Effect Of Turbulence Modelling In Numerical Analysis Of Melting Process In An Induction Furnace

Abstract: In this paper, the velocity field and turbulence effects that occur inside a crucible of a typical induction furnace were investigated. In the first part of this work, a free surface shape of the liquid metal was measured in a ceramic crucible. Then a numerical model of aluminium melting process was developed. It took into account coupling of electromagnetic and thermofluid fields that was performed using commercial codes. In the next step, the sensitivity analysis of turbulence modelling in the liquid domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
(11 reference statements)
0
9
0
Order By: Relevance
“…the upper part of the PIVIC setup (combustion chamber) was excluded. The modeling approach is similar to the one adopted in [16,20,23,25,26]…”
Section: Numerical Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…the upper part of the PIVIC setup (combustion chamber) was excluded. The modeling approach is similar to the one adopted in [16,20,23,25,26]…”
Section: Numerical Modelingmentioning
confidence: 99%
“…The problem of simulations of magnetohydrodynamics coupled with the cal-culation of the shape of the metallic charge is not new, and has been reported, for example, in metallurgy. Employed numerical methods were based on the mesh deformation [11][12][13][14] or used the volume of fluid (VOF) models [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous numerical studies of the research team [4], this coupling procedure was developed and examined for different operating conditions and material properties [5]. The last investigation [6], which was the most comprehensive analysis, indicated that the proposed mathematical model and coupling procedure yields reasonable accuracy in terms of the heat transfer and free surface prediction despite its simplicity.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used formulations are those based on the Reynolds-averaged Navier-Stokes (RANS) model. One paper [8] gives an analysis of the influence of different turbulence equations on the shape of the free surface of liquid metal. Turbulence intensity and its impact on the evaporation of components of the melt were examined as well [9].…”
Section: Introductionmentioning
confidence: 99%